Akibat Hukum Terhadap Pihak Ketiga Atas Pengangkatan Direksi dan Dewan Komisaris Yang Tidak Diberitahukan Kepada Menteri Hukum dan Ham Republik Indonesia - Hemi Marihot Goldfirst Nainggolan; Tofik Yanuar Chandra; Bernard Nainggolan (JOURNAL of LEGAL RESEARCH, 2022)
The nomination of a Limited Liability Company's Board of Directors and Board of Commissioners must be informed to the Minister of Law and Human Rights, as specified in Articles 94 and 111 of Law No. 40 of 2007 respecting Limited Liability Companies. Following compliance with these criteria, the Board of Directors and the Board of Commissioners are effectively appointed externally and are authorized to enter into legal relationships with other parties. The research method employed is a normative juridical one, with a statutory, conceptual, and case-based approach. The study's findings indicated that the legal consequences for third parties of not notifying the Ministry of Law and Human Rights of the Republic of Indonesia about the appointment of the Board of Directors and the Board of Commissioners resulted in the cancellation of a legal relationship between a third-party and the Board of Directors and the establishment of legal protection for third parties, namely that a third party could sue the Board of Directors, the Board of Commissioners.